ANALISIS FATWA DSN MUI NO: 123/DSN-MUI/XI/2018 TERHADAP PENGGUNAAN DANA TBDSP DI BTPN SYARIAH PERIODE TAHUN 2020-2023 - Diana Restu Cahyani; M. Lathoif Ghozali (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Bank Tabungan Pensiunan Negara (BTPN) also develops BTPN with Sharia principles. Islamic banking management also has funds that cannot be recognized as income (TBDSP), the TBDSP funds are used for community social activities. In receiving and distributing TBDSP funds to Sharia Banks, the National Sharia Board (DSN) of the Indonesian Ulema Council (MUI) issued Fatwa Number 123/DSN-MUI/XI/2018. The purpose of this article is to analyze the implementation of Fatwa DSN MUI No. 123/DSN-MUI/XI/2018 against the use of TBDSP funds. This research uses qualitative methods with a literature study approach. The data used was obtained from BTPN Syariah's annual performance report for the 2020-2023 period, the website of the Indonesian Ulema Council (MUI), the website of the Financial Services Authority (OJK) and the Central Statistics Agency (BPS). As a result of this research, BTPN Syariah has implemented fatwa DSN MUI Number 123/DSN-MUI/XI/2018 in managing TBDSP funds for the 2020-2023 period by using these funds for social activities. In distributing TBDSP funds, BTPN Syariah helps communities affected by Covid 19 and assists the government in the recovery and empowerment of MSMEs after Covid 19. This implementation is that the use of TBDSP funds by BTPN Syariah does not contradict sharia principles, as stipulated in Fatwa DSN MUI Number 123/DSN-MUI/XI/2018.